Economic Shocks and Household Consumption Smoothing Strategies - Céspedes Reynaga, Nikita (2024)
This paper examines the ability of Peruvian households to smooth consumption in the face of job loss and family business failure shocks, using the weak form of the permanent income hypothesis. The analysis distinguishes between ex ante mechanisms—such as insurance coverage and access to formal credit markets—and ex post responses adopted after a shock occurs. The results show that:(i) on average, households are able to smooth consumption; (ii) this ability is concentrated among those with access to the formal financial system, although some smoothing was also observed during the pandemic among households with informal savings; (iii) households tend to smooth spending on essential categories, such as food and health, but not on non-essential items including clothing, education, and leisure; in the case of health, smoothing is observed only when households have insurance coverage; and (iv) eight types of ex post coping strategies are evaluated, most of which help mitigate consumption losses-particularly multiple jobholding and government transfers. The findings also reveal substantial heterogeneity: higher-income households benefit from broader access to financial instruments, including severance savings, while lower-income households face more limited options and display weaker smoothing capacity.